Effects of schema therapy and schema-focused mindfulness therapy on marital satisfaction, marital communication and conflict resolution among Iranian women in Malaysia - Nooshin, Nooroney (2017)
This study aimed to investigate the effectiveness of schema therapy and schema-focused mindfulness therapy on marital satisfaction, marital communication and conflict resolution of Iranian married women who lived in Malaysia during 2015-2016. Some studies reported that a significant number of Iranian immigrants in Malaysia have a considerable concern about their marriage and show low marital satisfaction and weak conflict resolution ability because of the new situation, which they encounter after moving to Malaysia. It has also been discussed and ascertained that low marital satisfaction and lack of constructive communication cause a lot of difficulties and problems among couples that may finally lead to divorce. However, couple therapy and educational interventions are not quite satisfying to help couples and prevent distress. Therefore, psychologists and counsellors have to do more research in this field and increase their knowledge about couples’ issues to find new and fresh methods, skills and strategies. Accordingly, schema therapy and schemafocused mindfulness therapy are two new methods that can be examined to help psychologists and counsellors to prevent divorce and enhance the quality of marriage. This study is an experimental design to investigate the effectiveness of schema therapy and schema-focused mindfulness therapy on marital satisfaction, marital communication and conflict resolution. In this research, population refers to all married Iranian women who lived in Malaysia in 2015-2016 and were interested in participating the treatment sessions and increasing the quality of their relationship. The qualified participants included 96 women who were assigned randomly into three groups: two experimental groups and a control group with 32 women in each group. The first experimental group received schema therapy and the second group received schema-focused mindfulness therapy while the control group did not receive any treatment. The instruments used in this research included marital satisfaction, marital communication and conflict resolution subscales from the ENRICH questionnaire, a demographic questionnaire and Young's schema questionnaire. Post-tests were administered after 18 sessions of treatments, and then follow-up tests were completed two months after the post-tests. Descriptive and inferential statistical analyses were used in this research and, two-way repeated measures ANOVA and ANCOVA were applied. In general, it can be derived from the statistical analysis of the two-way repeated measures ANOVA test that the findings of this study are acceptable. The findings showed that both schema therapy and schema-focused mindfulness therapy had significant effects on marital satisfaction, marital communication and conflict resolution. The results were almost the same among schema therapy group and schema-focused mindfulness therapy group in the post-test. However, after two months follow-up, the differences revealed that the results in the second group, i.e. schema-focused mindfulness therapy group, have significantly improved during the time, while the results in the first group, i.e. schema therapy group, have remained constant. It means that mindfulness strategies gradually affected and the results of the second group were improved after a period. The findings of this study ascertained the fact that there are many advantages in schema therapy and schema-focused mindfulness therapy for couple therapists and they can use them more to increase the quality of marriages. It means that counsellors can use schema therapy and schema-focused mindfulness therapy in work with clients in order to improve their adjustment and function in the marriage, which are the main concerns of guidance and counselling.